Hitpig [videorecording (DVD)] - Rosenbaum, Dave (Production manager); Werrin, Tyler; Breathed, Berke; Summers, Isabella, 1980-; Skjenna, Olaf (Viva Pictures, 2025)
With a million dollars at stake, Hitpig's next job is to return an elephant to her maniacal Las Vegas show owner. But when the mission goes sideways, Hitpig must realize that no amount of money is worth losing his newfound friends.